Reflection of the Concept of the Meaning of Life on Mental Health In The Lyrics of Teramini's Songs - Nourma Ayu Safithri Purnomo. (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2026)
Mental health is an interesting topic to discuss in the digital age. Many media outlets discuss the concept of mental health, one of which is through literary works in the form of music. Music, which consists of various song lyrics, can be a medium of expression for conveying messages about an individual's psychological condition. One of the variables that plays an important role in the realization of mental health is the meaning of life and song titles that describe the concept of meaning of life, such as Teramini by Ghea Indrawari.  This study aims to deeply reflect on the concept of meaning of life in the lyrics of "Teramini," which has a positive impact on mental health, a topic that has not been explored previously. This study employs Viktor Frankl's theory of meaning in life, which explains that the sources of meaning in life consist of attitudinal, experiential, and creativity values. The object of this study is the lyrics of "Teramini." This study uses a qualitative method with thematic analysis as the analytical technique. Thematic analysis was chosen to understand the appropriate themes of the source of meaning in life from each lyric of the song Teramini. The results of this study indicate that the dominant source of meaning in life in the song Teramini is attitudinal values, followed by experiential values. Creativity values was not found in this study. Through the attitudinal and experiential values, individuals are able to accept all difficulties and view them as part of life's episodes, enabling them to endure and face them effectively, which positively impacts mental health. The findings of this study also indicate that literary works in the form of song lyrics can serve as an effective educational tool to provide an understanding of the concept of sources of meaning in life that influence mental health among listeners or community